Marshall McLuhan et la théorie médiatique : genèse, pertinence et limites d’une contribution contestée - Oumar KANE (Tic & Société)
The hermeticism and aphoristic style of Marshall McLuhan probably affected the scientific reception of his work. Nevertheless, the writings of the Canadian author still continue to attract both criticisms and praise. In this paper, we provide a brief account of his contribution. After reviewing some of the ideas of thinkers to whom McLuhan himself is indebted, we address the posterity of his writings and evoke the most recurrent criticisms of his work. The paper ends by mentioning how McLuhan imported approaches mobilized in literary theory in the 1930s into media analysis and by calling on Harold Innis’ approach to complement that of McLuhan.